Credit Guarantee Optimization of State-owned Enterprises - Chaisuekul, Chayanisa (Thammasat Review of Economic and Social Policy, 2018)
The objective of this paper is to estimate the credit risk of stateowned enterprises (SOEs) in the form of probability of default (PD) and then use it to analyze credit guarantee optimization. Estimation of the probability of default by the Hybrid Model found that the estimated PD for both financial and nonfinancial SOEs are ranked by credit rating grade (the rank ordering property), except for the 3rd rating grade PD of nonfinancial SOEs. Analysis of the optimal credit guarantee for each SOE by Linear Programming model found that the results of maximizing the net benefit and the results of minimizing the net expected loss from credit guarantee are similar. Moreover, the value of expected loss implies that the magnitude of credit risk must be mitigated and managed with appropriate tools by the Ministry of Finance.